Investigating The NTT Teachers in Facing The Online Teaching Challenges - Teofanne Nurinik Wea; Markus Budiraharjo (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
This study explored the challenges and the way how the teachers cope with their challenges. This study is a qualitative study which employed a narrative inquiry. Six participants from two different schools in NTT were participated in this study. They were English teachers, German teacher, mathematics teacher, history teacher and Geography teacher. In gathering the data, the researcher did a deep interview with the participants through Whatsapp voice note. In analyzing the data, the researcher did an interview transcript to note the participants’ responses. The researcher found that the participants had some difficulties in doing online learning such as their own ability about technology, students’ participation, students’ devices and ineffective learning. From those difficulties, they have a good self regulation to make a management time in order to make an effective learning and motivate the students to ignore their boredom. However, there was still a teacher who still had lack self efficacy since she had low ability in applying the technology devices in online learning. She had less confidence in doing online learning.